Prognosis of the probability of the development of deviant behavior among HIV infected with non-psychotic mental disorders based on multiple logistic analysis. - O. M. Hnenna (Medičnì Perspektivi, 2020)
The coexistence of psychopathological symptoms with HIV / AIDS is associated with aggravation of their condition due to the likelihood of deviant behavior. The aim of the study – assessment of the likelihood of deviant behavior in HIV-positive patients with non-psychotic psychiatric disorders. A comprehensive clinical and psychodiagnostic examination of 114 HIV-infected patients with non-psychotic psychiatric disorders was conducted including clinical-diagnostic interviews, pathopsychological and experimental-psychological methods of investigation, including the method of Ch.D. Spielberger in modification of Yu.L. Hanin (STAI - State-Trait Anxiety Inventory) for assessing anxiety level, Beck Depression Inventory (BDI-II) for assessing depression, SCL-90-R (Symptom Checklist 90-Revised) for assessing psychiatric symptoms. Statistical processing of the results was performed using descriptive and analytical methods implemented in the software STATISTICA 6.1 (StatSoftInc., Serial No. AGAR909E415822FA). Frequency and severity of depression and anxiety in HIV-infected persons is significant and by 3.4-4 times exceeds the corresponding indicators of a healthy Ukrainian population. Anxiety, depression, and other psychopathological symptoms according to SCL90-R scales (except for the obsessive-compulsive scale) are more pronounced in HIV-infected patients with destructive behavior than in patients without it. The chances of developing deviant behavior in HIV-infected persons with non-psychotic psychiatric disorders are increased at GSI>1 by 20.0 times (95% CI 5.63 - 71.07), in the presence of depressive symptoms – by 6.76 times (95% CI 2.16 – 21.18) and at a high level of personal anxiety – by 4.61 times (95% CI 2.05 - 10.40). Psychopathological symptoms of people with HIV status are characterized by high rates of depression and anxiety, somatization, paranoid ideas, interpersonal sensitivity. In patients with signs of deviant behavior, the severity of these disorders and the severity index of psychopathological symptoms was significantly higher (p<0.001) compared with patients who do not have such characteristics. According to the logistic prognostic model, the chance of developing deviant behavior significantly increases with an increase in the index of overall severity of psychopathological symptomatology, with an increase in the level of depression, and a level of personal anxiety. Considering this, when providing medical assistance to HIV-infected people, their needs for psycho-correction should be taken into account in order to prevent deviant behavior.